Neurobiological roots of language in primate audition: common computational properties. Issue 3 (March 2015) - Bornkessel-Schlesewsky, Ina; Schlesewsky, Matthias; Small, Steven L.; Rauschecker, Josef P.
Highlights: We present a unified dual-streams model for primate audition and human language. Dorsal/ventral stream computations in language are grounded in primate audition. Ventral stream: auditory object recognition and commutative combinatorics. Dorsal stream: hierarchical predictive coding of sequences from phonemes to discourse. Abstract : Here, we present a new perspective on an old question: how does the neurobiology of human language relate to brain systems in nonhuman primates? We argue that higher-order language combinatorics, including sentence and discourse processing, can be situated in a unified, cross-species dorsal-ventral streams architecture for higher auditory processing, and that the functions of the dorsal and ventral streams in higher-order language processing can be grounded in their respective computational properties in primate audition. This view challenges an assumption, common in the cognitive sciences, that a nonhuman primate model forms an inherently inadequate basis for modeling higher-level language functions.